2009
DOI: 10.4067/s0718-221x2009000100002
|View full text |Cite
|
Sign up to set email alerts
|

Creep Behavior of Borate-Treated Strandboard: Effect of Zinc Borate Retention, Wood Species, and Load Level

Abstract: Creep performance of zinc borate-treated strandboard from southern pine (Pinus taeda L.) and red oak (Quercus falcata) was investigated at 25°C temperature and 65% relative humidity. It was shown that the borate treatment had some signifi cant effect on creep defl ection of the test panels, and the effect varied with wood species. There was no signifi cant effect of creep loading on residual bending properties of treated strandboard under the stress levels used. The four element spring-dashpot creep model fi t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…10,23 The increased stress levels increase the deflection values as expected. 24 In this work, it was also found that the applied stress levels affect the creep behavior of the OSBs and the 55% stress levels produce more accurate results when compared to actual data. This can be related to the amount of loading required to get more accurate response from the OSBs.…”
Section: Long-term Performance Test Resultsmentioning
confidence: 65%
“…10,23 The increased stress levels increase the deflection values as expected. 24 In this work, it was also found that the applied stress levels affect the creep behavior of the OSBs and the 55% stress levels produce more accurate results when compared to actual data. This can be related to the amount of loading required to get more accurate response from the OSBs.…”
Section: Long-term Performance Test Resultsmentioning
confidence: 65%
“…The study of the creep behavior of materials such as polymer fibers, Raffia vinifera fibers, wood and composites has been approached using some rheological models such as Maxwell, Kelvin, Zener and Burger. 32,33…”
Section: Methodsmentioning
confidence: 99%
“…32 The study of the creep behavior of materials such as polymer fibers, Raffia vinifera fibers, wood and composites has been approached using some rheological models such as Maxwell, Kelvin, Zener and Burger. 32,33 Table 1 summarizes some rheological models used for the creep behavior. We note the presentation of the different models as well as their respective expressions.…”
Section: Study Of Creep Behaviormentioning
confidence: 99%
“…Using experimental data for tested Groups I and II in this study, stress equivalency coefficients, a, b and c, were calculated using Levenberg-Marquart (LM) algorithm, namely: Nonlinear Least Squares Minimization (Betten, 2008, Bewick, 2003. The values of these constants are listed in Fridley (1992) presented the following creep model (Wu 2009;Pierce 1977) as the original form of the four-element model presented in Equation 5.15 before simplifying it by Taylor (1996) in the form of creep constants A 1 , A 2 , A 3 and A 4 .…”
Section: Proposed Viscoelastic Creep Modelmentioning
confidence: 99%